A neuroendocrine carcinoma with a well-differentiated adenocarcinoma component arising in Barrett’s esophagus: a case report and literature review - Shunsuke Doi; Sohei Matsumoto; Kohei Wakatsuki; Kazuhiro Migita; Masahiro Ito; Tomohiro Kunishige; Hiroshi Nakade; Kinta Hatakeyama; Chiho Ohbayashi; Masayuki Sho (Surgical Case Reports, 2018)
Abstract Background An esophageal neuroendocrine carcinoma arising in Barrett’s esophagus is extremely rare. Here, we report a case of an esophageal neuroendocrine carcinoma with a well-differentiated adenocarcinoma component arising in Barrett’s esophagus and review the literature. Case presentation A 71-year-old man with no symptoms was admitted to our hospital because of the detection of an esophagogastric junction tumor on regular upper endoscopy screening. Endoscopy revealed a sliding hiatal hernia and an approximately 10 mm elevated mass at the esophagogastric junction. Biopsy showed a moderately differentiated tubular adenocarcinoma. Computed tomography did not indicate lymph node metastasis or distant metastasis. Proximal gastrectomy with D1 lymph node dissection was performed along with jejunal interposition. On immunohistochemical staining, the tumor was positive for chromogranin A and synaptophysin. Ki-67 was positive in 40% of the tumor cells. The histological diagnosis was a neuroendocrine carcinoma with a well-differentiated adenocarcinoma component arising in Barrett’s esophagus. The postoperative course was good, and the patient was discharged on the twentieth postoperative day. He has remained free of the disease at 36 months postoperatively. Conclusions Barrett’s esophagus may be related to the development of a neuroendocrine carcinoma.